Odpowiedź :
Odpowiedź:
Wyjaśnienie:
[tex]g_z=9,81\frac{m}{s^2}[/tex]
[tex]g_M=3,70\frac{m}{s^2}[/tex]
[tex]l_1=l_2=l[/tex]
[tex]szukane:\frac{T_z}{T_M}[/tex]
[tex]T_z=2\pi \sqrt{\frac{l}{g_z} }/^2[/tex]
[tex]T_z^2=4\pi^2\frac{l}{g_Z}[/tex]
[tex]T_M=2\pi \sqrt{\frac{l}{g_M} }/^2[/tex]
[tex]T_M^2=4\pi^2\frac{l}{g_M}[/tex]
[tex]\frac{T^2_z}{T_M^2}=\frac{4\pi^2\frac{l}{g_Z} }{4\pi \frac{l}{g_M} }=\frac{l}{g_Z}*\frac{g_M}{l}=\frac{g_M}{g_Z}[/tex]
[tex]\frac{T_z}{T_M}=\sqrt{\frac{g_M}{g_Z} }[/tex]
[tex]\frac{T_z}{T_M}=\sqrt{\frac{3,70\frac{m}{s^2} }{9,81\frac{m}{s^2} } }\approx0,61[/tex]
[tex]Dane:\\l_{z} = l_{m} = l\\g_{z} = 9,81\frac{m}{s^{2}}\\g_{m} = 3,70\frac{m}{s^{2}}\\Szukane:\\\frac{T_{m}}{T_{z}}=?\\\frac{T_{z}}{T_{m}}=?\\\\\\T = 2\pi \sqrt{\frac{l}{g}}\\\\T_{m} =2\pi \sqrt\frac{l}{g_{m}}\\\\T_{z} = 2\pi \sqrt{\frac{l}{g_{z}}[/tex]
[tex]\frac{T_{m}}{T_{z}} = \frac{2\pi \sqrt{\frac{l}{g_{m}}}}{2\pi\sqrt{\frac{l}{g_{z}}}}=\sqrt{\frac{g_{z}}{g_{m}}} = \sqrt{\frac{9,81}{3,70}}\\\\\\\boxed{\frac{T_{m}}{T_{z}} \approx2,65}[/tex]
[tex]\frac{T_{z}}{T_{m}} = \sqrt{\frac{g_{m}}{g_{z}}} = \sqrt{\frac{3,70}{\sqrt{9,81}}}\\\\\\\boxed{\frac{T_{z}}{T_{m}}\approx0,61}[/tex]